Combined Metabonomic and Quantitative RT-PCR Analyses Revealed Metabolic Reprogramming Associated with Fusarium graminearum Resistance in Transgenic Arabidopsis thaliana - Chen, Fangfang; Liu, Caixiang; Zhang, Jingtao; Lei, Hehua; Li, He-Ping; Liao, Yu-Cai; Tang, Huiru (Frontiers in Plant Science, 2018)
Fusarium head blight disease resulting from Fusarium graminearum (FG) infection causes huge losses in global production of cereals and development of FG-resistant plants is urgently needed. To understand biochemistry mechanisms for FG resistance, here, we have systematically investigated the plant metabolomic phenotypes associated with FG resistance for transgenic Arabidopsis thaliana expressing a class-I chitinase (Chi), a Fusarium-speciﬁc recombinant antibody gene (CWP2) and fused Chi-CWP2. Disease indices, mycotoxins, metabonomic characteristics and expression levels of several key genes were measured together with their correlations. We found that A. thaliana expressing Chi-CWP2 showed much higher FG resistance with much lower disease indices and mycotoxin levels than the wild-type and the plants expressing Chi or CWP2 alone. The combined metabonomic and quantitative RT-PCR analyses revealed that such FG-resistance was closely associated with the promoted biosynthesis of secondary metabolites (phenylpropanoids, alkanoids) and organic osmolytes (proline, betaine, glucose, myo-inositol) together with enhanced TCA cycle and GABA shunt. These suggest that the concurrently enhanced biosyntheses of shikimate-mediated secondary metabolites and organic osmolytes be an important strategy for A. thaliana to develop and improve FG resistance. These findings provide essential biochemical information related to FG resistance which may be of importance for developing FG-resistant cereals.